Anthropometry and competitive sport in Hungary - Mészáros, János (Acta Biologica Szegediensis, 2000)
Sport anthropometry has developed from the techniques and results of general physical anthropology. Thus, in the beginning, the main questions and methods were also similar to those of general physical anthropology, only the investigated subjects were taken of a different population. Following the initial, mainly descriptive and comparative, phases of data manipulation, the predictive functions of sport anthropometry have also developed. Continuous progress in the methods of sport training, consequently in athletic performances and the changes in athletic rules and equipment, have developed a need for the investigation of such (indirect) human biological factors that may have a role in competitive sport performance. The analytical approach in sport anthropometry has only become dominant during the past 10 years. A clear recognition of the relationship between structural characteristics and functions can &endash; beyond the scientific importance of the matter &endash; help sports practice in both the selection of talented youngsters and the process of athletic preparation. The most recent tendencies in sport anthropometry attempt to answer such questions that cannot be connected to the direct and traditional measurements of physical anthropology. An analysis of the relationship between inherited characteristics (physique and metabolic pathways, functional regulation during exercise, etc.) means a new challenge for sport anthropometry.